2018
DOI: 10.1177/0308022618777219
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between time spent in volunteering activities and quality of life in adults over the age of 50 years: A systematic review

Abstract: Introduction: Increased attention has focused on the importance of time spent by ageing adults in volunteering. The aim of this systematic review was to analyse literature exploring the relationship between time spent volunteering and quality of life for adults over the age of 50 years. Method: Electronic searches of nine databases located relevant articles involving adults over the age of 50 in volunteering activities that included psychological, physical and social quality of life domains. The quality of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 36 publications
(125 reference statements)
2
30
0
Order By: Relevance
“…Since that time, the field of Positive Psychology has thrived, with thousands of studies on virtues, strengths, positive emotions, and positive communities and workplaces. We see this explosion of studies in reviews and meta-analyses on signature strengths and virtues (Schutte and Malouff, 2019 ), helping behavior (Lefevor et al, 2017 ), creativity (Acar et al, 2020 ), resilience (Liu et al, 2020 ), positive affect and broaden and build theory (Fredrickson, 2013 ), forgiveness (Wade et al, 2014 ), flow (Harris et al, 2021 ), gratitude (Boggiss et al, 2020 ), self-compassion (Wilson et al, 2019 ), passion (Pollack et al, 2020 ), mindfulness (Fjorback et al, 2011 ), hope (Griggs, 2017 ), optimism (Rozanski et al, 2019 ), meaning in life (Manco and Hamby, 2021 ), volunteering (Milbourn et al, 2018 ), positive forms of motivation (Ntoumanis et al, 2021 ), value affirmation (Howell, 2017 ), school-based positive interventions (Tejada-Gallardo et al, 2020 ), workplace positive interventions (Donaldson et al, 2019 ), and other forms of positive intervention (Carr et al, 2020 ). This research has led to a broadening of the definition of positive psychology itself, with theorists arguing that positive psychology needs to include both positive and negative constructs and needs to consider a wider number of methodologies and levels (e.g., group, culture, etc.…”
mentioning
confidence: 99%
“…Since that time, the field of Positive Psychology has thrived, with thousands of studies on virtues, strengths, positive emotions, and positive communities and workplaces. We see this explosion of studies in reviews and meta-analyses on signature strengths and virtues (Schutte and Malouff, 2019 ), helping behavior (Lefevor et al, 2017 ), creativity (Acar et al, 2020 ), resilience (Liu et al, 2020 ), positive affect and broaden and build theory (Fredrickson, 2013 ), forgiveness (Wade et al, 2014 ), flow (Harris et al, 2021 ), gratitude (Boggiss et al, 2020 ), self-compassion (Wilson et al, 2019 ), passion (Pollack et al, 2020 ), mindfulness (Fjorback et al, 2011 ), hope (Griggs, 2017 ), optimism (Rozanski et al, 2019 ), meaning in life (Manco and Hamby, 2021 ), volunteering (Milbourn et al, 2018 ), positive forms of motivation (Ntoumanis et al, 2021 ), value affirmation (Howell, 2017 ), school-based positive interventions (Tejada-Gallardo et al, 2020 ), workplace positive interventions (Donaldson et al, 2019 ), and other forms of positive intervention (Carr et al, 2020 ). This research has led to a broadening of the definition of positive psychology itself, with theorists arguing that positive psychology needs to include both positive and negative constructs and needs to consider a wider number of methodologies and levels (e.g., group, culture, etc.…”
mentioning
confidence: 99%
“…As discussed previously, in healthy older adults, engaging in self-care occupations is important but so too is participation in leisure and productive occupations [ 15 – 17 , 19 , 20 ]. Cancer and its treatments can lead to functional limitations, especially among older adults [ 35 ], which can affect occupational engagement [ 36 ], especially as cancer can become a chronic disease [ 37 ], thus with long-term occupational disruptions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 34% of the women and 5% of the men were interested in productivity (e.g., household management) and about 90% of men and women were interested in quiet leisure. Finally, another study showed that American older adults could spend up to 1878 hours per year in mean in volunteering, with positive outcomes on quality of life [ 20 ], while in Sweden older workers over the age of 65 looked for a “harmonious mix of occupations.”…”
Section: Introductionmentioning
confidence: 99%
“…Engagement in voluntary work provides wide-ranging benefits for individual mental and social wellbeing [3,6,7]. A report from the National Council for Voluntary Organisations (NCVO) showed that 96% of volunteers (N = 10,103) reported feeling happy with the experience, with 9 in 10 reporting that volunteering provided enjoyment, a sense of personal achievement and purpose [3].…”
Section: Of 15mentioning
confidence: 99%
“…Engaging in voluntary work is also associated with improved physical health. Reported physical benefits include decreased rates of functional decline, reduced cortisol reactivity to stressors and lower cardiovascular risk; as well as increased physical activity, strength and walking speed [6,[10][11][12]. Volunteering also offers opportunities to widen social networks, enhance social bonds and connectedness, and it may provide social rewards [6,13,14].…”
Section: Of 15mentioning
confidence: 99%